Urinary exosomes from patients with diabetic kidney disease induced podocyte apoptosis via microRNA-145-5p/Srgap2 and the RhoA/ROCK pathway - Lulu Han; Shenghai Wang; Juan Li; Lulu Zhao; Hong Zhou (Experimental and Molecular Pathology, 2023)
Diabetic kidney disease (DKD) is a leading cause of end-stage renal disease without early diagnostic and specific therapeutic approaches. Podocyte apoptosis and loss play important roles in the pathological process of DKD. This study aimed to explore whether urinary exosomes from type 2 diabetes patients with DKD could induce podocyte apoptosis and the underlying pathological mechanisms. The exosomes were isolated from the urine samples of patients with DKD (DKD-Exo). Later, they were taken up and internalized by MPC5 cells. MPC5 cells were co-cultured with DKD-Exo (45 μg/ml) for 24 h in the presence or absence of microRNA-145-5p (miR-145-5p) inhibitor, fasudil and pcDNA-Srgap2 transfection. MiR-145-5p and Srgap2 expression was evaluated using real-time quantitative PCR. The protein levels of Srgap2, Bcl-2, Bax, and cleaved caspase-3, as well as ROCK activity were determined using Western blotting. Cell apoptosis was measured using flow cytometry and the TUNEL assay. miR-145-5p expression in MPC5 cells exposed to DKD-Exo was markedly upregulated. miR-145-5p negatively regulated Srgap2 levels. Exposure of MPC5 cells to DKD-Exo reduced Srgap2 expression and activated ROCK, which was partly reversed by the presence of the miR-145-5p inhibitor or Srgap2 overexpression. The apoptosis of MPC5 cells exposed to DKD-Exo increased significantly, which was counteracted by the addition of the miR-145-5p inhibitor and fasudil. The results showed that urinary exosomal miR-145-5p from patients with DKD induced podocyte apoptosis by inhibiting Srgap2 and activating the RhoA/ROCK pathway, suggesting that urinary exosomal miR-145-5p is involved in the pathological process of DKD and could become a noninvasive diagnostic biomarker for DKD.